Antihypertensive and Antioxidant Activity of Herbal Medicine (Jamu) B on Rats Induced by 10% Fructose - Eff, Aprilita Rina Yanti; Ayu Pertiwi, Reza; Ehe Hurit, Hermanus; Rahayu, Sri Teguh; Eden, Yonatan (Pharmaceutical Sciences and Research, 2022)
Prolonged fructose intake can activate the renin-angiotensin-aldosterone system and enhance oxidative stress conditions, causing hypertension and hyperuricemia. This study aimed to determine the antihypertensive and antioxidant activity of Jamu B on the activity of superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA) in the kidneys of Sprague Dawley rats induced by 10% fructose. Thirty rats were divided into six groups. Groups B1-B3 were Jamu groups at a dose of 0.12 g/kg BW (B1), 0.24 g/kg BW (B2), and 0.36 g/kg BW (B3); group C (positive control) was given captopril 0.1 g/kg BW, group D (negative control) was given only 10% fructose, and group E (normal control) was healthy rats. The 10% fructose was induced for eight weeks and the treatment was given at the week 9th and 10th. Jamu B reduced systolic and diastolic blood pressure at all doses, but not significantly different from the normal control group (p>0.05). The SOD activity in groups B1, B2, B3, and C was significantly different from the negative control group (pJamu B at dose of 0.12 g/kg BW; 0.24 g/kg BW; and 0.36 g/kg BW have antihypertensive and antioxidant activity in the kidneys of rats induced by 10% fructose. Nevertheless, Jamu B at a dose of 0.36 g/kg BW was the most effective as an antihypertensive and antioxidant.